Pengaruh Pemberian Teh Kombucha Konsentrasi 50% dengan Waktu Fermentasi yang Berbeda pada Struktur Histologi Hepar Tikus Wistar (Rattus norvegicus) Jantan - Isdadiyanto, Sri; Tana, Silvana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
This study was conducted to determine the effect of 6 kombucha fermented tea (P1), 9 (P2) and 12 (P3) fermentation days at a concentration of 50% on the liver histological structure and hepatocyte diameter. This study used 16 male white rats consisting of 4 treatments and 4 replications. The treatment of this study consisted of P0: control treatment; P1, P2 and P3 respectively were given 6, 9 and 12 days fermented kombucha tea at a concentration of 50%. This research uses a completely randomized design. The variable measured in this study was the diameter of hepatocytes in test animals. The data obtained were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level and if there were real differences, followed by Duncan's test. The results of data analysis showed that kombucha tea fermented 6, 9 and 12 days with a 50% concentration did not have a significant difference in hepatocyte diameter variables. The histological structure of the liver looks normal and shows no sign of cell damage. It can be concluded that kombucha tea at a concentration of 50% is safe for consumption by mammals because it does not cause liver damage.